EFFECTIVE STAFF PERSONNEL ADMINISTRATION AS PREDICTOR OF TEACHERS’ JOB INVOLVEMENT IN SECONDARY SCHOOLS IN ANAMBRA STATE (Journal of Association of Educational Management and Policy Practitioners, 2024)
The study which established the effective staff personnel administration as predictor of teachers‘ job involvement in public secondary schools in Anambra State was anchored on one research question and one hypothesis. Design used for the study was correlation while the population of the study comprised all the public secondary schools in Anambra State numbering 266 with 5133 teachers made up of 756 males and 4377 females. Using stratified random sampling technique, 2456 teachers were selected which is 47.8%. Instrument for data collection was a questionnaire type designed by the researcher entitled ―Effective Staff Personnel Administration as Predictor of Teachers‘ Job Involvement Questionnaire‖ (ESPAPTJIQ). The instrument has two sections: Staff Personnel Administrator Scale (SPAS) which contained 10 questionnaire items and was used to gather data on the independent variable of the study while the second section was tagged ―Teachers‘ Job Involvement Scale (TJIS) and contained 10 questionnaire items and was used to collect data on the dependent variable of the study. The instrument was face and content validated using experts in relevant fields. The average reliability of SPAS was 0.82 while that of TJIS was 0.80 using regression analysis statistics. Pearson Product Moment Correlation Method was used for the data analysis to answer the research question. The findings revealed that there is a low positive relationship existing between teachers‘ perception of principals‘ effective staff personnel administration and teachers‘ job involvement in public secondary schools in Anambra State. Based on the findings, it was recommended that the government should set up special intervention programmes geared at sensitizing principals on the need for effective school administration as this will improve teachers‘ job involvement through striving to stick to ethical standards.